Survey of Chenopodiaceae family from Taif, Saudi Arabia Peninsula - Mohammad Moneruzzaman, Khandaker; Ali, Majrashi (2020)
Weeds are consider as a significant important biological indicator of crop production resulting to yield loss of about 50%. Identification of weeds is very difficult from their morphological features. Despite weeds are the real challenge in farming in the developed, developing and underdeveloped countries. Nevertheless, weeds are also part of primary producers. Major constrain of crop production are weeds but they are also consider as important aspect of agricultural system in the world. Weeds are wild plants grow in an environment without the contribution of any human activities that have positive or negative impact to the environment. The aim of the study is to documents weeds of family Chenopodiaceae and agricultural crops grown in Taif region of Saudi Arabian kingdom in a mountain with an elevation level of (Area A = Al sail 1700 m, Area B = Al Wahat and Al Watit 1500 m, C = Leeih 1500 m, D = AL Gaim and Saisad 1500 m, F = E = Al Shafa 2200 m, F = AL Hada = 2000 m). The study was carried out based on environmental survey. Diverse number of weeds were identified and collected from the examined study area. Results revealed aggressive weeds species. Atriplex leucoclada, Chenopodium valria, Chenopodium album, Chenopodium murale, Chenopodium vulvaria, Chenopodium mavele, Dysphania ambrosioides and Lamb’s quarters with the total number of 1727. Chenopodium vulvariawas found with the highest number of species 553, follow by Chenopodium album 394 and the least is Lamb’s quarters 17. The study, similarly, documented 12 agricultural crops weeds from the study area; Portulaca oleracea, Raphanus sativus, Phoenix dactylifera, Mentha, Rosa damascena, Solanum melongena, Petroselinum sp, Zea mays, Cauliflower, Vitis spp, Brassica oleracea var. capitate and Cucurbita pepo. Findings from the study will aid management control and proposing research toward improved new weed control measures. Also has provided insight on purposeful weeds control in Taif Area.